The Impact of Working Conditions on the Workers in Foundry Production - Aleksander Mikhailovich, Lazarenkov; Metchislav Antonovich, Sadokha; Ihar Arkadzevich, Ivanou (INTI International University, 2025)
This article examines the impact of working conditions on the health of foundry personnel. The study explores the effects of various production factors, such as dust, gas pollution, noise, vibration, and microclimate parameters, on workers in different areas of foundry workshops. The analysis also covers the state of occupational morbidity among personnel, taking into account the type of production (mass, batch, and small-batch). The findings reveal that the highest number of occupational diseases were detected in the cleaning, molding, melting and casting departments of foundries. The most affected professions include casting dressers, molders, smelters, melter-pourers, and repairmen. These results highlight the significant health risks associated with working conditions in these areas and underscore the need for improved safety measures and health monitoring in foundry environments.